An innovative model for management of cardiovascular disease risk factors in the low resource setting of Cambodia. Issue 4 (25th December 2020) - Nikpour Hernandez, Nazaneen; Ismail, Samiha; Heang, Hen; van Pelt, Maurits; Witham, Miles D; Davies, Justine I
Abstract: Non-communicable diseases are increasing in developing countries and control of diabetes and hypertension is needed to reduce rates of the leading causes of morbidity and mortality, stroke and ischaemic heart disease. We evaluated a programme in Cambodia, financed by a revolving drug fund, which utilizes Peer Educators to manage diabetes and hypertension in the community. We assessed clinical outcomes and retention in the programme. For all people enrolled in the programme between 2007 and 2016, the average change in blood pressure (BP) and percentage with controlled hypertension (BP < 140/<90 mmHg) or diabetes (fasting blood glucose (BG) < 7mg/dl, post-prandial BG < 130 mg/dl, or HBA1C < 7%) was calculated every 6 months from enrolment.  Attrition rate in the nth year of enrolment was calculated; associations with loss to follow-up were explored using cox regression. A total of 9139 patients enrolled between January 2007 and March 2016. For all people with hypertension, mean change in systolic and diastolic BP within the first year was −15.1 mmHg (SD 23.6, P < 0.0001) and −8.6 mmHg (SD 14.0, P < 0.0001), respectively. BP control was 50.5% at year 1, peaking at 70.6% at 5.5 years. 41.3% of people with diabetes achieved blood sugar control at 6 months and 44.4% at 6.5 years.  An average of 2.3 years [SD 1.9] was spent in programme. Attrition rate within year 1 of enrolment ranged from 29.8% to 61.5% with average of 44.1% [SD 10.3] across 2008–15. Patients with hypertension were more likely to leave the program compared to those with diabetes and males more likely than females. The programme shows a substantial and sustained rate of diabetes and hypertension control for those who remain in the program and could be a model for implementation in other low middle-income settings, however, further work is needed to improve patient retention.